Primera hembra conocida de Megathecla gigantea (Hewitson, 1867) (Lepidoptera: Lycaenidae: Eumaeini) - Lamas, Gerardo (2004)
The first known female of the extremely rare Amazonian species Megathecla gigantea (Hewitson, 1867) (Lepidoptera: Lycaenidae: Eumaeini), from Peru, Loreto, Tierra Hermosa is reported herein. Some notes are given on its behavior and habitat.